Effects of stretching exercises on muscle tension, fatigue, strength, and lactic acid accumulation: A pre-experimental study among fish transport workers - Kurniawan, Bina; Rahfiludin, Mohammad Z.; Setyaningsih , Yuliani; Nurjazuli , Nurjazuli; Lestantyo , Daru; Widjasena , Baju; Jayanti , Siswi (Narra Sains Indonesia, 2024)
Fish transport workers in Indonesia lift loads more than the specified limits, both in weight and frequency. This could cause lactic acid accumulation, fatigue and reduced physical performance. The aim of this study was to assess the effect of stretching intervention on muscle tension, fatigue, strength, and lactic acid level in fish transport workers in Indonesia. A pre-experimental study design with one group (pre- and post-test) design was conducted among male fish transport workers at the Tawang fish auction, Weleri, Central Java, Indonesia, in June 2022 for two weeks. We created a 1.5-minute stretching exercise video based on the University of New Castle's Manual Handling guideline, involving hand, feet, and shoulder movements. Participants performed these exercises independently before and during work every two hours, guided by the video. Data on lactic acid, muscle tension, fatigue, and strength were collected before and after the 2-week intervention. Data analysis was performed using Wilcoxon and paired Student t-tests to compare the outcome between post- and pre-intervention. A total of 18 fish transport workers were included in the study. The results showed a statistically significant increase in lactic acid levels following the intervention (p=0.016). However, the increase in muscle tension was not statistically significant (p=0.292). There was a significant increase in fatigue levels after the intervention (p=0.000). This could suggest that the stretching intervention may have had an unintended effect of increasing fatigue among the participants. On the other hand, there was a statistically significant decrease in muscle strength after the intervention (p=0.003). In conclusion, this study suggests that while stretching exercises can affect lactic acid accumulation, fatigue, and muscle strength, they do not influence muscle tension. Therefore, it is advised for workers to incorporate stretching exercises into their daily routine to mitigate potential injury risks.